University violence and its relationship to the academic compatibility of university students - م. م ژيان جمال عثمان أ.د ساهرة رزاق كاظم (physical education and sport sciences college for women/ Baghdad University, 2021)
The study aimed to identify the degree of university violence                               and academic compatibility and the relationship between them, and to distinguish the differences between males and females in the degree of university violence and academic compatibility with the research sample. The descriptive approach was used on a sample of students from the Faculties of Computer Science and the College of Business Administration at Cihan University For the academic year (2018-2019) ,They were randomly selected from the fourth and third (male-female) students, whose number is (200) male and female students (100) male and (100) female students, and the two research criteria (university violence, psychological harmony) were applied and the results of the two measures were handled by the statistical program system ( SPSS) version (V24), the following conclusions have been reached: The students of Cihan University suffer from an increase in the rate of university violence and poor academic compatibility, and there is an inverse relationship between university violence and academic compatibility, and the study showed the superiority of males over females in the behavior of university violence, and showed the superiority of females over males to the variable of academic compatibility.